1995
DOI: 10.1161/01.cir.92.5.1193
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Electrophysiological Behavior of Human Atria During Paroxysmal Atrial Fibrillation

Abstract: The analysis of the FF intervals demonstrates a strict correlation with atrial functional refractoriness. The self-termination of atrial fibrillation is related to a prolongation of the functional refractoriness (mean FF), whereas a shortening of both functional and effective refractoriness (fifth percentile) is associated with atrial fibrillation persistence. The provoked shortening of the mean FF at the stimulation site is consistent with the presence of a gap of excitability during atrial fibrillation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(110 citation statements)
references
References 21 publications
11
96
2
1
Order By: Relevance
“…We also observed that the significant reduction in the 5th percentile of the VV intervals, refractory period, and wavelength and the significant increment in activation map complexity obtained in the control series during stretch were significantly reduced by the Na ϩ /Ca 2ϩ exchanger blocker. The similar variations in the 5th percentile of the VV intervals and refractory period agree with the results of a previous study (5) in which the 5th percentile has been proposed as a surrogate measurement of the effective refractory period during VF. On the other hand, frequency and timedomain techniques supply analogous information in the analysis of VF activation frequency as previously seen (6,8,41), although the presence of double and multiple potentials can condition DF values (8).…”
Section: Effects Of the Na ϩ /Ca 2ϩ Exchanger Blocker Kb-r7943supporting
confidence: 90%
“…We also observed that the significant reduction in the 5th percentile of the VV intervals, refractory period, and wavelength and the significant increment in activation map complexity obtained in the control series during stretch were significantly reduced by the Na ϩ /Ca 2ϩ exchanger blocker. The similar variations in the 5th percentile of the VV intervals and refractory period agree with the results of a previous study (5) in which the 5th percentile has been proposed as a surrogate measurement of the effective refractory period during VF. On the other hand, frequency and timedomain techniques supply analogous information in the analysis of VF activation frequency as previously seen (6,8,41), although the presence of double and multiple potentials can condition DF values (8).…”
Section: Effects Of the Na ϩ /Ca 2ϩ Exchanger Blocker Kb-r7943supporting
confidence: 90%
“…Firstly, the DAF, which has been described in Section § 3. Its inverse has been directly related to atrial refractoriness [64] and, hence, to atrial cycle length [5]. Moreover, it has been suggested that the DAF is directly related to the number of simultaneous wavelets [65].…”
Section: Surface Organization Methodsmentioning
confidence: 99%
“…En este sentido, se han postulado métodos alternativos para cuantificar la refractariedad local en fibrilación [Duytschaever et al 2001]. Entre ellos, aquel que asocia el percentil 5 del histograma de intervalos entre activaciones sucesivas (intervalo VV) a un indicador de refractariedad, por estar relacionado tanto con el periodo refractario funcional como con el efectivo [Capucci et al 1995, Duytschaever et al 2001. Esto, unido a la posibilidad de realizar la detección automática de los instantes de activación -referida en el subapartado 1.1.4-, hace que dicho indicador pueda resultar ventajoso para cuantificar la refractariedad frente a otros más complicados de llevar a 7 Se define en el subapartado 4.2.2.…”
Section: Refractariedad Y Longitud De Onda En Fvunclassified